Overexpression of src family gene for tyrosine-kinase p59fyn in CD4-CD8- T cells of mice with a lymphoproliferative disorder. - Katagiri, T (1989)
Overexpression of a src family gene, lck, has been associated with differentiation of the murine thymic lymphoma line LSTRA. Recent findings by several groups strongly suggest a functional role for the gene product p56lck protein-tyrosine kinase (PTK) in the activation of normal T cells. A single recessive gene, lpr or gld, induces a lymphoproliferative disorder concomitant with autoimmune disease in mice. In this study, a 10-fold elevated activity of PTK encoded by fyn, another src family gene, was demonstrated in CD4-CD8- T cells in mutant mice. The increased PTK activity was consistent with overexpression of fyn mRNA. The elevated fyn mRNA expression appeared to be a characteristic of CD4-CD8- T cells, since it was not observed in normal T cells at any stage of differentiation. The fact that fyn mRNA expression was markedly induced in normal T cells by mitogenic stimulation with anti-T3 epsilon antiserum supports the possibility that p59fyn PTK is a signal-generating molecule in T cells. Thus, our findings provide insight into the physiological role for a src gene family kinase in T-cell development and contribute to a better understanding of the molecular mechanisms of disease-inducing recessive genes.